Current insights into hormonal regulation of microspore embryogenesis - Żur, Iwona; Dubas, Ewa; Krzewska, Monika; Janowiak, Franciszek (Frontiers in Plant Science, 2015)
Plant growth regulator (PGR) crosstalk and interaction with the plant’s genotype and environmental factors play a crucial role in microspore embryogenesis (ME), controlling microspore-derived embryo differentiation and development as well as haploid/doubled haploid plant regeneration. The complexity of the PGR network which could exist at the level of biosynthesis, distribution, gene expression or signaling pathways, renders the creation of an integrated model of ME-control crosstalk impossible at present. However, the analysis of the published data together with the results received recently with the use of modern analytical techniques brings new insights into hormonal regulation of this process. This review presents a short historical overview of the most important milestones in the recognition of hormonal requirements for effective ME in the most important crop plant species and complements it with new concepts that evolved over the last decade of ME studies.